(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The role of psychological methods in managing the activities of a physical education teacher. Teaching the effective use of psychological methods in teaching physical education lessons to preschool, school, and vocational college teachers, sports coaches, educators, and mentors.